A comparative investigation on the bioaccumulation of heavy metal ions by growing Rhizopus arrhizus and Aspergillus niger - Dursun, AY; Uslu, G; Tepe, O; Cuci, Y; Ekiz, HI (Elsevier Science Sa, 2003)
The bioaccumulation of Cu(II) and Cd(H) ions by viable Rhizopus arrhizus and Aspergillus niger was studied as a function of initial pH and initial metal ion concentration. Optimum pH values for maximum Cu(II) and Cd(II) accumulation were determined, respectively, as 4.5 and 3.5 for R. arrhizus and 5.0 and 3.0 for A. niger. Although both the metal ions caused an inhibition effect on the growth of the microorganisms, R. arrhizus and A. niger were capable of removing Cu(II) with the maximum specific uptake of 10.76 and 9.53 mg g(-1) at 75 mg dm(-3) initial Cu(II) concentration, respectively. R. Arrhizus was found to be more resistant and efficient to accumulate larger amounts of Cd(II) than A. niger at all Cd(II) concentrations. A. niger was totally inhibited by 50 mg dm(-3) initial Cd(II) concentration. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: bioaccumulation; Cu(II); Cd(II); Rhizopus arrhizus; Aspergillus niger